PENGARUH KOMUNIKASI DAN LINGKUNGAN ORGANISASI TERHADAP KINERJA PEGAWAI DI KANTOR KEMENTERIAN AGAMA KABUPATEN BULUKUMBA - Asfiadi Asfiadi (Manajemen Pendidikan, 2020)
This research aims to analyze and examine the influence of communication and organizational environment to employee performance at Ministry of Region Office, Bulukumba District, South Sulawesi. This study is a quantitative research with ex post facto method. The participants of this research are 52 employees from Ministry of Region Office, Bulukumba District. Data collection technique with questionnaires and then analyzed by using regression analysis to test the hypothesis. The results of this study show that partially, the organizational communication has a positive effect on employee performance of 27,5%, as well as the organizational environment has a positive effect on employee performance of 49,4%. Simultaneously, organizational communication and environment has a positif effect on employee performance of 52,1% and 47,9% is determined by other factors. Thus, communication and organizational environment are the factors that determine the level employee performance. Key word: Communication, Organizational Environment, and Employee Performance